Integrated Method for Purification and Single-Particle Characterization of Lentiviral Vector Systems by Size Exclusion Chromatography and Tunable Resistive Pulse Sensing - Heider, Susanne (Mol Biotechnol, 2017)
Elements derived from lentiviral particles such as viral vectors or virus-like particles are commonly used for biotechnological and biomedical applications, for example in mammalian protein expression, gene delivery or therapy, and vaccine development. Preparations of high purity are necessary in most cases, especially for clinical applications. For purification, a wide range of methods are available, from density gradient centrifugation to affinity chromatography. In this study we have employed size exclusion columns specifically designed for the easy purification of extracellular vesicles including exosomes. In addition to viral marker protein and total protein analysis, a well-established single-particle characterization technology, termed tunable resistive pulse sensing, was employed to analyze fractions of highest particle load and purity and characterize the preparations by size and surface charge/electrophoretic mobility. With this study, we propose an integrated platform combining size exclusion chromatography and tunable resistive pulse sensing for monitoring production and purification of viral particles. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12033-017-0009-8) contains supplementary material, which is available to authorized users.